2017
DOI: 10.1088/1367-2630/19/1/013028
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate charge ordered states in thett′–Jmodel

Abstract: We study the incommensurate charge ordered states in the ¢ -t t J model using the Gutzwiller mean field theory on large systems. In particular, we explore the properties of incommensurate charge modulated states referred to as nodal pair density waves (nPDW) in the literature. nPDW states intertwine site and bond charge order with modulated d-wave pair order, and are characterized by a nonzero amplitude of uniform pairing; they also manifest a dominant intra-unit cell d-density wave form factor. To compare wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 45 publications
(127 reference statements)
5
51
0
Order By: Relevance
“…In fact, numerous different phases have been obtained by investigating Hubbard and t-J type Hamiltonians in attempts to find the proper theoretical description of high-T c cuprates [22][23][24][25][26][27][28][29][30][31][32], revealing low-energy intertwined inhomogeneous states, such as stripes, bidirectional charge-ordered states, checkerboard patterns, and so on. Recently, tensor network studies [33] and density matrix embedding theory [34] provided new evidence that the ground state (GS) of the Hubbard model could indeed be inhomogeneous at finite doping and that its phase diagram shows co-existence of d-wave superconducting (SC) order with other instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, numerous different phases have been obtained by investigating Hubbard and t-J type Hamiltonians in attempts to find the proper theoretical description of high-T c cuprates [22][23][24][25][26][27][28][29][30][31][32], revealing low-energy intertwined inhomogeneous states, such as stripes, bidirectional charge-ordered states, checkerboard patterns, and so on. Recently, tensor network studies [33] and density matrix embedding theory [34] provided new evidence that the ground state (GS) of the Hubbard model could indeed be inhomogeneous at finite doping and that its phase diagram shows co-existence of d-wave superconducting (SC) order with other instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the previous work of Capello et al [19] on the same model using variational Monte Carlo. Finally, the pair density wave (PDW) state has been the focus of many studies [20][21][22][23][24] (for a recent review, see Ref. [25]).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the superfluid density ρS(r) shows a checkerboard pattern indicative of the PDW state, and it shares a common wavevector with the checkerboard charge order. The most probable scenario was proposed to be the coexisting of d-wave symmetry superconductivity and d-symmetry form factor CDW.If the PDW state is such a pronounced feature as revealed in the SJTM, one would expect that it should also manifest itself in single particle tunneling spectroscopy probed by plain STM.An obvious strategy is to investigate the spatial distribution of SC gap size, but recent theories show that the SC gap size may not show spatial periodicity even if there is PDW order [24][25][26][30][31][32] . Here we propose that there are two other key characteristics associated with superconductivity in a single particle tunneling spectrum.…”
mentioning
confidence: 99%
“…An obvious strategy is to investigate the spatial distribution of SC gap size, but recent theories show that the SC gap size may not show spatial periodicity even if there is PDW order [24][25][26][30][31][32] . Here we propose that there are two other key characteristics associated with superconductivity in a single particle tunneling spectrum.…”
mentioning
confidence: 99%